2021
DOI: 10.2147/jmdh.s325645
|View full text |Cite
|
Sign up to set email alerts
|

Telepharmacy: A Potential Alternative Approach for Diabetic Patients During the COVID-19 Pandemic

Abstract: The use of telepharmacy technology allows pharmacists to provide clinical pharmaceutical services to patients with diabetes mellitus (DM) who need regular services during the COVID-19 pandemic while maintaining distance and minimizing face-to-face meetings. The purpose of this review article was to identify the impact of telepharmacy intervention by pharmacists in diabetic patients by reviewing clinical outcomes and patient therapy adherences. A literature search was conducted through the PubMed database using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
2
18
0
3
Order By: Relevance
“…Nonetheless, we must take into account that, in reality, not all patients have the same needs. [34][35][36] Many facts could explain this gap; firstly, the study was conducted via an online survey-based that was distributed through social media platforms inclining the study to selection bias, capturing mainly feedback from the younger population while underrepresenting the elderly, which are the population category that may benefit from home delivery of medication services. Secondly, the majority of participants were active young adults who can visit retail pharmacies and do not need easier access to get their medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we must take into account that, in reality, not all patients have the same needs. [34][35][36] Many facts could explain this gap; firstly, the study was conducted via an online survey-based that was distributed through social media platforms inclining the study to selection bias, capturing mainly feedback from the younger population while underrepresenting the elderly, which are the population category that may benefit from home delivery of medication services. Secondly, the majority of participants were active young adults who can visit retail pharmacies and do not need easier access to get their medicines.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study that implemented this strategy showed that this short-term switch did not impact the efficacy or safety of chronic management of warfarin therapy (Cope et al, 2021). In patients with diabetes, 11 studies showed positive clinical outcomes following telepharmacy services provided by ambulatory care pharmacists, where telephone calls were the mostly used technology followed by electronic messages (Iftinan et al, 2021). Most of the services included providing patient counseling and monitoring medication adherence.…”
Section: Specialized Clinical Pharmacistsmentioning
confidence: 99%
“…A recent study on telepharmacy for diabetes care found that most of the interventions were delivered via telephone and were associated with improved access to health care, a reduction in the need for physical consultations, better diabetes control (a significant decrease in HbA1c), and improved medication adherence. 39 Importantly, those interventions with less patient engagement (a call for 5 min within 2–3 weeks of the intervention) and those compared to other telehealth interventions led by another HC provider, e.g., nurses, were less likely to show a significant impact. 39 By providing remote value-added services, promoting healthy lifestyle changes, reminding for necessary monitoring and annual screenings, and encouraging patients to maintain continuity of care, telepharmacy enabled pharmacists to demonstrate their empathy-based professional support for diabetes care.…”
Section: Introductionmentioning
confidence: 99%
“… 39 Importantly, those interventions with less patient engagement (a call for 5 min within 2–3 weeks of the intervention) and those compared to other telehealth interventions led by another HC provider, e.g., nurses, were less likely to show a significant impact. 39 By providing remote value-added services, promoting healthy lifestyle changes, reminding for necessary monitoring and annual screenings, and encouraging patients to maintain continuity of care, telepharmacy enabled pharmacists to demonstrate their empathy-based professional support for diabetes care. 15 It is critical to emphasize that telepharmacy has the potential to spread rapidly in low- and middle-income countries if proper training, arrangements, and compensation are considered.…”
Section: Introductionmentioning
confidence: 99%